IDENTITY CONSTRUCTION OF THE MINORITY PAPUAN MUSLIM - Musa Rumbaru;; Surwandono; Hasse; Ridho (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2018)
This article explores contemporary development of a minority of Muslim in the largest Muslim country Indonesia. It closely examines the minority Muslim Papuan and looks at the construction and the institutionalisation of Muslim identity in post-special autonomy (otonomi khusus) of Papua. Through a series of fieldwork in Jayapura, the capital of the Papua Province, in 2016 and reviews of documents, the article argues that the Council of Papuan Muslim (Majelis Muslim Papua/MMP) serves not only a the association of minority Muslim Papuan but also as a political instrument for the minority to fight for equality in Papuan public sphere. Importantly, the Muslim Papuan try reconcile the popular, but contradicted, notion of Muslim -and Islam- as newcomer -if not to mention as the colonial- in Papua and the presence of Muslim as a symbolic expectation for progress of the Papuan in general. Thus, the institutionalization of Islam, through the establishment of The Majelis Muslim Papua in Papua resorts as an ample case where multiculturalism is tested in contemporary Indonesia.